2021
DOI: 10.1108/ijem-05-2020-0258
|View full text |Cite
|
Sign up to set email alerts
|

I am engaged, therefore my students are satisfied! Unleashing the role of teachers' interaction and sensitivity based on self-determination perspective

Abstract: PurposeStudents' satisfaction is termed as their subjective evaluation of the fulfillment of expectations and pleasure experienced from the teaching services. This study intends to examine the role of teachers' work engagement in inculcating students' satisfaction from their teachers taking a self-determination perspective. It moreover highlights the underlying mechanisms of teacher–student interaction and teachers' sensitivity.Design/methodology/approachWe used 278 valid and matched responses from teachers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Student satisfaction is defined as the feeling of pleasure or fulfilment that students obtain from the educational services and experience received (Bilal et al, 2020). It is the level of satisfaction that students have with their programme of study.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Student satisfaction is defined as the feeling of pleasure or fulfilment that students obtain from the educational services and experience received (Bilal et al, 2020). It is the level of satisfaction that students have with their programme of study.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The literature has identified of positive outcomes of teachers' work engagement, which has been associated with a lower intention to quit the profession (Skaalvik and Skaalvik, 2016), higher student satisfaction (Bilal et al ., 2020). Prior results concerning technostress indicate that it is also associated with several teaching-related outcomes, such as poorer work performance (Li and Wang, 2021), lower intention of to use educational technology (Joo et al ., 2016) as well as less adoption and use of digital textbooks (Verkijika, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of an academic institution, students are service consumers, and as far as student satisfaction is concerned, it is shaped by experiences of students having used the facilities of a campus, the perceived performance quality in terms of teaching and services rendered, the university’s reputation and attributes of the social community. Regardless of the activities that take place in a university, effective teaching is considered crucial and the most important stakeholders to be the torchbearers of service provision would be its lecturers (Bilal et al, 2021) .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective teaching in the e-learning realm has to do with a few factors, namely, expertise in using e-tools to enhance learning, student interaction and creating an innovative and comfortable atmosphere to cultivate closer relationships between students and lecturers (Coman et al, 2020) (Hamdan et al, 2021) Research has shown a positive correlation between online learning provided and its effectiveness, it is said to be just as effective and better in certain situations compared to the traditional face-to-face teaching because in situations where students are introverted, shy and easily intimidated, they were able to learn better (Condon and Ruth-Sahd, 2013). However, most students are studying in isolation through e-learning, thus the lecturer’s active, positive interaction and sensitivity towards students would be a determining factor in enhancing their satisfaction (Bilal et al, 2021) (Rogers and Smith, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%